Dampak Ketergantungan Media Sosial pada Kalangan Dystopian dan Utopian - Irianti, Een (Communicatus: Jurnal Ilmu komunikasi, 2017)
Media creates a dependency for its users, it seemed to have become a common sight in media studies at this time. many theories that explain the influence of media on audiences that make audiences are addicted to media such as the theory of hypodermic needles, dependency theory, the theory of cultivation and much more, penguruh media that are considered capable of poisoning the minds of the audience that makes the audience helpless in the face of media exposure , The focus of this article is "Impact of Addiction Social Media in circles Dystopian and Utopian" which will be described in the sub-focus, namely: the impact of social media for the Dystopian, the impact of social media for the utopian, meaning the Dystopian and Utopian put on social media and expression and Dystopian circles and utopian representation in social media.